HfO2 thin film formed by solution-coating method and application to resistive switching device. (7th January 2021) - Ban, Takahiko; Matsumura, Ryota; Yamamoto, Shin-ichi
Abstract: The characteristics of a resistive-switching RAM (ReRAM) device are investigated using a HfO2 thin film. HfO2 is prepared using the solution-coating method. In the HfO2 -precursor solution, hafnium isopropoxide is used as a solute and ethylene glycol monomethyl ether as a solvent. Additionally, diethanolamine (DEA) is used as a chemical modifier. The solution is prepared by adjusting the solvent to achieve concentrations of 0.1 mol l −1, 0.5 mol l −1, and 0.5 mol l −1 + DEA (4 eq). After applying the solution on Pt, the films are obtained by spin coating and sintering. The HfO2 -ReRAM is fabricated using Al as the top electrode, and bipolar properties are obtained for all three concentrations. A fabricated HfO2 -ReRAM device with an average thickness of approximately 28 nm exhibits a ON/OFF current ratio of 10 4 . In the high-resistance state, conduction is mainly due to the Pool–Frenkel conduction and Schottky emission, whereas in the low-resistance state, conduction is mainly ohmic.